Increased Brain Age Gap Estimate (BrainAGE) in Young Adults After Premature Birth - Hedderich, Dennis M.; Menegaux, Aurore; Schmitz-Koep, Benita; Nuttall, Rachel; Zimmermann, Juliana; Schneider, Sebastian C.; Bäuml, Josef G.; Daamen, Marcel; Boecker, Henning; Wilke, Marko; Zimmer, Claus; Wolke, Dieter; et al. (Frontiers in Aging Neuroscience, 2021)
Recent evidence suggests increased metabolic and physiologic aging rates in premature-born adults. While the lasting consequences of premature birth on human brain development are known, its impact on brain aging remains unclear. We addressed the question whether premature birth impacts on brain age gap estimates (BrainAGE) using an accurate and robust machine-learning framework based on structural MRI in a large cohort of young premature-born adults (n=101) and full-term controls (n=111). Study participants are part of a geographically defined population study of premature-born individuals, which have been followed longitudinally from birth until young adulthood. We investigated the association between BrainAGE scores and perinatal variables as well as with outcomes of physical (total intracranial volume, TIV) and cognitive development (full-scale IQ, FS-IQ). We found increased BrainAGE in premature-born adults (median [interquartile range] = 1.4 [-1.3-4.7 years]) compared to full-term controls (p=0.002, Cohen’s d = 0.443), which was associated with low gestational age, low birth weight and increased neonatal treatment intensity but not with TIV or FS-IQ. In conclusion, results demonstrate elevated BrainAGE in premature-born adults, suggesting an increased risk for accelerated brain aging in human prematurity.